Introduction of Nitrogen Fixing Medicinal Plants: a Suitable Alternative for the Conservation of Exposed Sites in the Garhwal Himalayan Ecosystem - Parandial, A. K.; Kumar, Pankaj; Naithani, H. B.; Pokhriyal, T. C. (Indian Forester, 2005)
The Garhwal Himalayas are one of the richest floristic zones for the medicinal plants of Indian subcontinent. It provides matchless wealth of more than 300 rare and endangered species of medicinal plants having therapeutic properties. The over exploitation of these precious material from himalayan forest ecosytstem over last few decades have not only pushed these towards extinction but also enhanced the problem of soil erosion, land degradation and loss of biodiversity in the area. Introduction of nitrogen fixing plants may provide an important tool for the ecorestoration attempts in this area. Advocating nitrogen fixing plants having medicinal uses may provide wider acceptability among the local populace from economic as well as soil conservation point of view. The adoptability of indigenous species may be useful for planting and rejuvenating the degraded sites in different altitudinal zones of the Himalayan ecosystem. In the present article an attempt has been made to enumerate the existing nitrogen fixing species of medicinal values at various altitude for the conservation of degraded sites in Garhwal Himalayas.